2009
DOI: 10.1007/s10531-008-9573-3
|View full text |Cite
|
Sign up to set email alerts
|

How do roads affect the habitat use of an assemblage of scavenging raptors?

Abstract: Scavengers may benefit from the availability of dead animals along roads that result from collisions with vehicles. However, roads are also considered risky places for many species. Animal habitat selection patterns usually balance energy intake with mortality risk. In this work we analyzed the foraging space use of an assemblage of diurnal scavenging raptors in relation to distance from roads in northwest Patagonia. We selected patches at different distances from roads, and placed a sheep carcass in each patc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 26 publications
2
92
1
6
Order By: Relevance
“…Research has found that responses of different species vary, but total bird captures declined significantly at road edges as most birds are reluctant to cross a road (Develey & Stouffer 2001;Laurance et al 2004). Some birds however prefer roads (Dean & Milton 2003;Lambertucci et al 2009) so it seems specific species (Kuitunen et al 1998) or guilds (Forman & Alexander 1998;Kuitunen et al 1998;Laurance et al 2004) of birds are more affected. Among the various reasons proposed, including predators, visual disturbance and air pollutants, traffic noise seems to be the major cause for changes in avian community assembly (see review by Forman & Alexander 1998;Forman & Deblinger 2000;Peris & Pescador 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that responses of different species vary, but total bird captures declined significantly at road edges as most birds are reluctant to cross a road (Develey & Stouffer 2001;Laurance et al 2004). Some birds however prefer roads (Dean & Milton 2003;Lambertucci et al 2009) so it seems specific species (Kuitunen et al 1998) or guilds (Forman & Alexander 1998;Kuitunen et al 1998;Laurance et al 2004) of birds are more affected. Among the various reasons proposed, including predators, visual disturbance and air pollutants, traffic noise seems to be the major cause for changes in avian community assembly (see review by Forman & Alexander 1998;Forman & Deblinger 2000;Peris & Pescador 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Carcasses near roads are usually detected much faster than those far from roads, and scavengers may benefit from the availability of dead animals along roads that result from collisions with vehicles (Lambertucci et al, 2009). However, roads are also considered risky places for many species, and the actual increasing number of new roads in Qatar (Richer, 2008) will probably result in higher dhub mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The latter point could make more of these birds be exposed to collision with vehicles (Lambertucci et al, 2009;Husby, 2017 …”
Section: Richness and Diversity Of Birds Along Roadsmentioning
confidence: 99%